2021
DOI: 10.1136/oemed-2020-107276
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impact of the COVID-19 pandemic on 4378 UK healthcare workers and ancillary staff: initial baseline data from a cohort study collected during the first wave of the pandemic

Abstract: ObjectivesThis study reports preliminary findings on the prevalence of, and factors associated with, mental health and well-being outcomes of healthcare workers during the early months (April–June) of the COVID-19 pandemic in the UK.MethodsPreliminary cross-sectional data were analysed from a cohort study (n=4378). Clinical and non-clinical staff of three London-based NHS Trusts, including acute and mental health Trusts, took part in an online baseline survey. The primary outcome measure used is the presence o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
99
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 38 publications
11
99
2
Order By: Relevance
“…Worldwide studies have demonstrated very significant levels of anxiety, depression, insomnia and post-traumatic stress in healthcare workers with estimates of caseness ranging from 15 to 27% for depression, 12 to 23% for general anxiety and 30 to 35% for post-traumatic stress symptoms. 2,6 However, we do note a recent review of populations affected by COVID 17 that found no significant differences between healthcare workers and other populations affected by COVID-19 on measures of depression, anxiety and Fig. 1 Proportion of respondents with moderate-to-severe symptoms in the time 1 and 2 cross-sectional samples.…”
Section: Main Findings and Comparison With Findings From Other Studiesmentioning
confidence: 76%
See 3 more Smart Citations
“…Worldwide studies have demonstrated very significant levels of anxiety, depression, insomnia and post-traumatic stress in healthcare workers with estimates of caseness ranging from 15 to 27% for depression, 12 to 23% for general anxiety and 30 to 35% for post-traumatic stress symptoms. 2,6 However, we do note a recent review of populations affected by COVID 17 that found no significant differences between healthcare workers and other populations affected by COVID-19 on measures of depression, anxiety and Fig. 1 Proportion of respondents with moderate-to-severe symptoms in the time 1 and 2 cross-sectional samples.…”
Section: Main Findings and Comparison With Findings From Other Studiesmentioning
confidence: 76%
“…1 Unsurprisingly, these figures are elevated for UK healthcare workers because of the considerable professional demands placed on them over a long-term period, with estimates of 'caseness' (i.e. moderate-to-severe symptoms) at 27% for depression, 23% for general anxiety and 30% for post-traumatic stress symptoms 2 throughout the early stages of the pandemic. During the same time period, lower caseness estimates for depression (15%) and anxiety (12%), but higher rates of post-traumatic stress (35%) were reported among medical and nursing staff in China.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moral distress has been a prominent theme for healthcare workers during the pandemic. [134][135][136][137] In a study in the Netherlands, two sources of moral distress that increased in COVID-19 (scarcity of resources and the perception of colleagues acting unsafely) were significant predictors of burnout. 103 In a Toronto hospital, moral distress was strongly related to emotional exhaustion and accounted for most of the difference in burnout between roles (nurses vs. other health professionals vs. other staff with regular patient contact; Hunter J, personal communication).…”
Section: Moral Distressmentioning
confidence: 99%